The Roots of the United States' Cyber (In)Security. - Fuller, Christopher J (Diplomatic History, 2019)
The article traces the roots of U.S. cyber insecurity and explores the emergence of cyber security as a policy issue for the U.S. government. It highlights the proliferation of computer networks in the U.S. along with the adoption of encryption protocols during the administration of U.S. President Ronald Reagan in the 1980s. The vulnerability of computer networks to cyber attacks exposed the security flaws across the computer networks of the U.S. Department of Defense (DoD). A presidential directive required the transformation of the National Security Agency's (NSA) Computer Security Evaluation Center (CSEC) into the National Computer Security Center (NCSC). The National Telecommunications and Information Systems Security Committee (NTSISSC) was formed to intervene in cyber insecurity.